A05 Alterations in linear and back-splicing as new players in huntington's disease pathogenesis. (September 2018) - Ayyildiz, D; Dassi, E; Tripathi, T; Monziani, A; Kerschbamer, E; Pennati, E; Ferrarini, D; Donini, L; Leva, F di; Kovalenko, M; Zasso, J; Conti, L; et al.
Abstract : Background: Huntington's Disease (HD), is a hereditary, fatal neurodegenerative disorder due to CAG trinucleotide expansion in exon 1 of the HD gene (HTT). Recent findings revealed that the process of alternative splicing (AS) might be compromised in HD. AS regulation is crucial not only to the establishment of a repertoire of protein coding isoforms extremely relevant for the proper physiological characteristics of the nervous system, but also to the biogenesis of circular RNAs (circRNAs), unusually stable, highly expressed non-coding RNAs produced by the circularization of exons which, seems to have important roles during neuronal development and functioning. Aims: Therefore, the overarching goal of our research was to take advantage of genetically engineered Htt knock-in (KI) mouse cellular and in vivo model systems bearing normal or pathological Htt CAG repeat lengths to discover alterations in linear and back-splicing events that might reflect on the levels of expression as well as the composition of a repertoire of proteins, thus contributing to HD striatal vulnerability and pathogenesis. Methods/techniques: To discover alterations in linear splicing, we resourced to a publicly available dataset (Langfelder P. et al., 2016, Nature Neuroscience) analyzing full transcriptomic profiling dataset for striatum, cortex and liver at different developmental time points, identifying and quantifying the total numbers of differential AS events for each genotype/sample type and time point. Results/outcome: Our analysis demonstrated that specifically for the striatum – most vulnerable to HD degeneration – the total number of detected, differential AS events increased significantly at 6 and 10 month with increasing CAG expansion. Interestingly, not all the AS events increased with CAG-expansion and age, but only a specific subtype of AS event – EXON SKIPPING – revealed to be strongly and specifically affected. On the other hand, we identified and characterized the first circular RNA originating locally from the HTT locus, expressed in whole body, but predominantly in the brain and spinal cord and presenting augmented expression level with increasing HTT CAG size. Moreover, at genome-wide level, data analysis of circRNA-seq showed a decreased circRNAs production when mutant huntingtin is expressed. Specifically, 12 circRNAs, identified by stringent cut-off criteria, showed continuous decreased expression following CAG expansion in neuronal progenitor cells. Since, most of the CAG-sensitive circRNAs have annotated human orthologues, their expression can be further characterized and functionally studied in human cell lines. Conclusions: In conclusion, our results support the idea that AS machinery is responding to HD mutational process altering both linear and back-splicing events locally at the HTT locus, but also at genome-wide level. This knowledge will pave the way to new trials of therapeutic intervention aimed to possibly target spliceosomal-circRNAs alterations through specific drugs or genetic manipulation.